2016
DOI: 10.1002/ajh.24326
|View full text |Cite
|
Sign up to set email alerts
|

Is low‐molecular weight iron dextran really the most risky iron?—Unconvincing data from an unconvincing study

Abstract: The use of intravenous iron has expanded over the past few years as accepted indications for its use have increased. It is now recognized that intravenous iron will raise iron stores faster and more reliably in conditions in which oral iron is unlikely to work or poorly tolerated such as chronic kidney disease, inflammatory bowel disease, heavy uterine bleeding, hereditary hemorrhagic telangiectasia (Osler-Weber-Rendu), pregnancy, and those having undergone bariatric surgery. However, the acceptance of this ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 11 publications
0
18
0
1
Order By: Relevance
“…iron described as the Fishbane reaction [26,27]. The pathogenesis is unknown, but according to Rampton (2014), it is believed to be a complement activation-related pseudo-allergy (CARPA) triggered by iron nano-particles [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…iron described as the Fishbane reaction [26,27]. The pathogenesis is unknown, but according to Rampton (2014), it is believed to be a complement activation-related pseudo-allergy (CARPA) triggered by iron nano-particles [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…71 The major disadvantage with intravenous iron is infusion reactions, but both the incidence and severity of these is often overstated. 72 These reactions are not true allergic reactions but are related to complement activation by the labile free iron. 73 Recently detailed advice about treating these reactions has been published 74 ; in general, for mild reactions, the infusion is stopped and then resumed at a slower rate once symptoms resolve.…”
Section: Intravenous Ironmentioning
confidence: 99%
“…The investigators concluded that anaphylaxis was more likely with ID compared with iron sucrose. There are, however, concerns with the study: In the analysis, the authors were unable to distinguish between HMW‐ID and LMW‐ID, both of which continued to be available during the study. The administration of diphenhydramine and epinephrine were used as surrogates for anaphylaxis, and it was impossible to tell if they were used as premedication or as an unnecessary intervention for a minor, self‐limited infusion reaction. The average age of IV iron recipients analyzed was in the 1970s missing many frequent recipients of IV iron, including those with heavy uterine bleeding, pregnancy, bariatric surgery, and inflammatory bowel disease. Dialysis patients were also excluded, eliminating the lion's share of patients who received iron sucrose in the United States during the study period. Most importantly, from the article authors' own supplemental material online, the risk of death on the day of administration was an order of magnitude lower with ID than any of the other iron formulations, effectively contradicting the conclusions of their paper …”
Section: Historical Overviewmentioning
confidence: 99%
“…Most importantly, from the article authors' own supplemental material online, the risk of death on the day of administration was an order of magnitude lower with ID than any of the other iron formulations, effectively contradicting the conclusions of their paper. 10,11 Recently LMW-ID has been shown to be able to be administered safely and effectively as a 1000 mg dose in 1 hour in 888 patients who received 1266 doses, in a population of patients with iron deficiency caused by heavy uterine bleeding, bariatric surgery, inflammatory bowel disease, hereditary hemorrhagic telangiectasia and pregnancy. 12,13 A recent observational study in 189 oral iron intolerant, iron deficient gravidas in the second and third trimester reported hemoglobin responses in 92% without significant toxicity.…”
Section: Iron Dextranmentioning
confidence: 99%